Comparative Study of Flexural Behavior of Bolted-Laminated and Glue-Laminated Sengon Timber Beams (Albizia falcataria) - Yosafat Aji Pranata; Anang Kristianto; Novi Novi (Masyarakat Peneliti Kayu Indonesia, 2024)
This study aimed to study the flexural behavior of bolt-laminated and glue-laminated sengon (Albizia falcataria) timber beams, which are flexural strength, modulus of rupture (MoR), and beam ductility. The study was conducted using an experimental testing method in the laboratory with reference to the ASTM D198. The number of test objects were three consecutively for bolt-laminated beams and glue-laminated beams. Results obtained from this study indicated that the flexural strength of bolt-laminated and glue-laminated sengon timber beams was not significantly different; the flexural strength of bolt-laminated beams were 3.1% higher compared to glue-laminated beams. The MoR and ductility of bolt-laminated beams were 8.4% and 14.2% higher compared to glue-laminated beams. These results indicate that the glue has an impact to the brittle behavior or limited ductility, while the bolts have an impact to make a more ductile beams. The general conclusion is that mechanical laminated timber technology can be an alternative to producing beams with larger cross-sectional sizes compared to solid timber, especially for low-grade wood, so that it can be used as part of the structural elements of buildings.